2016
DOI: 10.1002/jbm.b.33692
|View full text |Cite
|
Sign up to set email alerts
|

A biological study establishing the endotoxin limit of biomaterials for bone regeneration in cranial and femoral implantation of rats

Abstract: The purpose of this study was to accurately quantify the risk of endotoxin contamination in biomaterials for bone regeneration in order to establish the acceptable endotoxin limit. Collagen sheets containing varying amounts of purified endotoxin from Escherichia coli and dried, heat-killed E. coli or Staphylococcus aureus cells were implanted into cranial or femoral defects in rats. These defects were artificially prepared to a size of 5 × 5 mm or a diameter of 1 mm, respectively. The degree of osteoanagenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…There have been several studies on the host response to biomaterials spiked with bacterial components such as endotoxin [26] , [27] , [28] , [29] , [30] , but none have focused on their effect on MSCs and dose response to establish endotoxin limits at specific sites of the body. In the only quantitative analysis to date, we reported that a collagen sheet containing dried E. coli cells implanted into a cranial or femoral defect in rats caused a dose-dependent delay in osteoanagenesis with a no-observed-adverse-effect level of 9.6 EU/mg, which did not occur with an untreated collagen sheet or one containing Staphylococcus aureus cells [21] . These results suggest that endotoxin affects the process of osteoanagenesis and that the delayed formation of new bone was caused by dried cells that suppressed the development of connective tissue covering the defective parts and the proliferation and differentiation of MSCs (intramembranous ossification), since a pathological analysis did not detect any osteoclasts or inflammation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There have been several studies on the host response to biomaterials spiked with bacterial components such as endotoxin [26] , [27] , [28] , [29] , [30] , but none have focused on their effect on MSCs and dose response to establish endotoxin limits at specific sites of the body. In the only quantitative analysis to date, we reported that a collagen sheet containing dried E. coli cells implanted into a cranial or femoral defect in rats caused a dose-dependent delay in osteoanagenesis with a no-observed-adverse-effect level of 9.6 EU/mg, which did not occur with an untreated collagen sheet or one containing Staphylococcus aureus cells [21] . These results suggest that endotoxin affects the process of osteoanagenesis and that the delayed formation of new bone was caused by dried cells that suppressed the development of connective tissue covering the defective parts and the proliferation and differentiation of MSCs (intramembranous ossification), since a pathological analysis did not detect any osteoclasts or inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…It should be noted that all items used for cell culture such as medium, serum, reagent, enzyme, scaffold, and plastic products (culture plate, pipet, and chip) may be contaminated with endotoxin even if they are labeled as endotoxin free. It may not be possible to estimate endotoxin levels when selecting serum lots, and scaffolds made from natural products—even those of high quality—may contain trace amounts; there has been at least one reported case of commercial enzymes such as collagenase contaminated with endotoxin [21] . SEIKAGAKU Corporation (Tokyo, Japan), a company that produces limulus amebocyte lysate reagents for endotoxin testing, has alerted consumers via their home page that commercially available plastic products labeled endotoxin free are occasionally contaminated with endotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…This was not observed when an untreated collagen sheet or one containing Staphylococcus aureus cells were used. These observations suggested that endotoxin affected the process of osteoanagenesis and that the delayed formation of new bone was caused by the dried cells that suppressed the development of the connective tissue covering the defective areas, as well as the proliferation and differentiation of MSCs (intramembranous ossification), since the pathology analysis did not reveal any osteoclasts or inflammation [28] . Thus, endotoxin exhibits different effects in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 98%
“…Several studies on the host response to biomaterials with spiked-in bacterial components, such as endotoxin, have been published [23] , [24] , [25] , [26] , [27] , but none have focused on their effect on MSCs or the dose response to establish endotoxin limits at specific sites of the body. In the only quantitative analysis published to date, we reported that a collagen sheet containing dried E. coli cells implanted into a cranial or femoral defect in rats led to a dose-dependent delay of the osteoanagenesis with a NOAEL of 9.6 EU/mg [28] . This was not observed when an untreated collagen sheet or one containing Staphylococcus aureus cells were used.…”
Section: Discussionmentioning
confidence: 98%
“…Um Estudo laboratorial demonstrou que o azul de toluidina pode se aderir fortemente ao LPS (USACHEVA;TEICHERT;BIEL, 2003). Sabe-se que o LPS pode interferir na resposta celular do tecido ósseo(HAISHIMA et al, 2016). A partir das observações de nossa pesquisa poderíamos lançar a hipótese de que a união LPS-azul de toluidina tornou o LPS inativo ou diminuiu sua ação de provocar dano celular e isso poderia ter aumentado o crescimento celular do grupo tratado com terapia fotodinâmica em relação aos outros grupos.…”
unclassified